Analisis Keandalan Pada Operator Grinding Menggunakan Metode Cognitive Reliability and Error Analysis di PT Ravana Jaya - Siti Nur Hasanah; Moch. Nuruddin (Fakultas Teknik, 2022)
PT Ravana Jaya is a company implementing construction services and steel plate fabrication. As for the activities of the steel plate fabrication process, labor makes direct contact with work activities that have a high risk of work accidents and are dangerous. Based on work accident report data from 2019 to 2021, the majority of work accidents occur in grinding activities caused by work conditions, operator experience and human error. The purpose of the study is to identify and analyze the factors of accidents that occur caused by human error using the CREAM method. The CREAM method is a method of analyzing human constraints that measures cognitive reliability and possible errors. The results showed that the cognitive function with the highest error value was found in the interpretation perspective of diagnosing inaccurate or incomplete data with a CFP value of 0.024 contained in Task 4.2 in the error mode ensuring the quality of the grinding stone in good condition and not cracked, Task 4.3 in the mode of ensuring that the rpm of the grinding stone is greater than the rpm of the grinding machine and Task 5.1 in the mode of checking the work area neatly before activities.